Role of nano-selenium and irrigation water quality in some anatomical and chemical characteristics of some citrus rootstocks - Alaa Abbas Ali; Ghalib Bhew Abud Al-Abbasi (Journal of Kerbala for Agricultural Sciences, 2024)
The research was carried out in a lath-house at Karbala certified citrus nursery/Department of Horticulture/Kerbala Agriculture Directotae, Hindiyah District, for the season 2022, starting from 1/3 to 1/11, to study the effect of spraying with Nano-selenium and water types for irrigation water on some anatomical and chemical characteristics of three citrus rootstocks. The experiment was three factors Split- Split Plot Design in R.C.B.D. The main plot was two types of water: river water and well water, sub-plot was three Citrus rootstocks, Sour orange, Volcamariana and Lime seedlings, while the sub-sub-plot included Spraying Nano selenium at a concentration of 0, 1, and 2 mg L-1. The result showed that the spraying with Nano-selenium at 2ml L-1 resulted in higher cuticle thickness, CHO%, proline acid, ABA hormone and Glutathione GSH. However, Nano-selenium and water quality did not show much effect on the average number of stomata in the leaves. For the water types, it showed that the irrigation with well water resulted in higher cuticle thickness, plant content of proline acid, ABA hormone and Glutathione GSH). Among the rootstocks, the Sour orange had the highest in plant content of proline acid, ABA hormone and Glutathione GSH, while Lime rootstock was the best in number of leaf stomata and CHO%, as the rootstocks didn’t differ in leaf cuticle thickness. The best results for the most indicators under study were obtained in the presence of Nano-selenium 2 mg L-1 where interacted with well water and Sour orange. Lime rootstock seedlings performed better with river water. This study showed that applying Nano- selenium 2 mg L-1 can be the best choice to improve seedlings growth and to enhance seedling tolerance to well water salinity.